2016
DOI: 10.1177/1069072715615849
|View full text |Cite
|
Sign up to set email alerts
|

The Working Alliance in Career Counseling

Abstract: The research related to the working alliance in career counseling is reviewed in this manuscript. This review indicates that the working alliance does typically increase over the course of career counseling. Furthermore in career counseling, most of the correlations between the working alliance and various outcome measures were significant and hovered around .30, which is consistent with findings related to the correlation between the working alliance and outcome in psychotherapy. In terms of factors that pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 44 publications
4
49
0
9
Order By: Relevance
“…This ingredient is inherent to the working alliance between client and counsellor. However, Whiston et al (2015) surmise that there is very little research about how to facilitate a working alliance in career counselling. The U-Cube is a tangible medium that connects the client and counsellor in a conversation and it is this conversation that becomes the grist of career exploration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ingredient is inherent to the working alliance between client and counsellor. However, Whiston et al (2015) surmise that there is very little research about how to facilitate a working alliance in career counselling. The U-Cube is a tangible medium that connects the client and counsellor in a conversation and it is this conversation that becomes the grist of career exploration .…”
Section: Discussionmentioning
confidence: 99%
“…Along with the critical five ingredients of career interventions' effectiveness (Brown et al, 2003), the working alliance is a key predictor of counselling outcomes (Masdonati, Massoudi, & Rossier, 2009;Whiston, Rossier, & Barón, 2015). Working alliance refers to the relationship between client and practitioner, and is a tripartite model made up of goals, tasks, and bonds.…”
Section: Introductionmentioning
confidence: 99%
“…These agreements are important because, on the one hand, clients are usually aware of their preferences related to career counseling before the intervention, but, on the other hand, they do not have clear ideas of what will occur during the career counseling process (Galassi et al, 1992;Niles et al, 2000). Many studies have demonstrated that the working alliance tends to increase during the career counseling process (see review by Whiston et al, 2016), and this increase positively affects the outcomes, including satisfaction with the intervention (Masdonati et al, 2014). Consequently, initial expectations are not enough for understanding the whole process through which clients perceive and evaluate a career counseling intervention.…”
Section: Impact Of Client Expectations On Career Counseling Satisfactionmentioning
confidence: 99%
“…Fostering a Working Alliance Investigating clients' responses on the item level may foster the working alliance that is critical to career counseling efficacy (Whiston, Rossier, Baron, & Hernand, 2016). According to Bordin (1979), the working alliance comprises three key factors: (a) agreement on the goals, (b) agreement on the tasks to achieve that goal, and (c) the emotional bond between counselor and client.…”
Section: Providing Feedbackmentioning
confidence: 99%